A study of forms of project organisation and matrix management: case studies from the construction industry - Bresnen, Michael J. (1986)
This study investigates the forms and processes of interaction that occur in the organisation and management of projects. It takes as its empirical focus of enquiry the situation in the UK construction industry; and uses, as its database, five case studies of medium to large-scale, 'one-off' construction projects.